Disentangling taxonomy of Biacetabulum (Cestoda, Caryophyllidea), parasites of catostomid fishes in North America: proposal of Megancestus gen. n. to accommodate B. carpiodi - Uhrovič, Dalibor; Scholz, Tomáš; Kudlai, Olena; Oros, Mikuláš (Parasitology research, 2021)
A new genus, Megancestus n. gen., is proposed to accommodate the caryophyllidean tapeworm Biacetabulum carpiodi Mackiewicz, 1969 from carpsuckers and quillback (Carpiodes spp.) in North America. This species is not closely related to other species of Biacetabulum Hunter, 1927 and is transferred to a newly erected genus. This new genus is typified by the possession of a small body (total length of 3.1-7.5 mm) with a scolex that bears a pair of large acetabulum-like loculi, two pairs of shallow lateral loculi, and a slightly convex apical disc, testes arranged in one or two layers, oval, thick-walled cirrus-sac, well-developed external seminal vesicle, separate gonopores, H-shaped ovary, few median vitelline follicles, and the uterus extending by a single loop anterior to the cirrus-sac. Megancestus differs from all Nearctic caryophyllidean genera (family Capingentidae), including Biacetabulum, by vitelline follicles dorsal to the ovary that connect the preovarian and postovarian vitelline fields. The most closely related Hunterella Mackiewicz et McCrae, 1962 differs by shape of the scolex (tholate, i.e., devoid of any loculi), dumbbell-shaped ovary and the uterus not extending anterior to the cirrus-sac. Megancestus carpiodi (Mackiewicz, 1969) n. comb. is the only species of the genus and it is a stenoxenous parasite, which has been found only in the river carpsucker (Carpiodes carpio-type host), quillback (Carpiodes cyprinus) and highfin carpsucker (Carpiodes velifer) (Catostomidae: Ictiobinae) in the lower and middle Mississippi basin.
Keywords: Eucestoda; Cestoda; fylogeneze; North America; SEM; Cestode Infections; Fish Diseases; Species Specificity; Comparative morphology; nemoci ryb; Animals; Nearctic Region; zvířata; máloostní; Taxonomy; Phylogeny; cestodózy; 28S rDNA; ženské pohlaví; Cypriniformes; Fish; Female; druhová specificita; Severní Amerika